A Business Process Modelling and Notation Meta-Model Approach to Enhance Prioritization for Decision-Making in Requirement Engineering - Muhamad Idaham, Umar Ong; M. A., Ameedeen (Universiti Teknikal Malaysia Melaka (UTeM), 2016)
It is has always been the main focus of requirements engineer in making sure a set of optimal requirements is prepared in development of a project. With the current issue of getting the desired result, engineers would prioritize the set of requirements and utilize this to produce a list of optimal requirements. This paper will discuss some introduction of the evolution of software requirements prioritization, some related works, approach of conducting the research and finally discussing the expected result of this research. The outcome of this research should be able to justify the need of prioritizing requirements based on its root that is business process.